PENGETAHUAN, KEPATUHAN, DAN PENDIDIKAN UNTUK MENCEGAH PENYEBARAN PENYAKIT CORONAVIRUS (COVID-19) - Thaslifa; Andis Sugrani; Yanti Sunaidi; Mutmainnah Abbas; Resi Agestia Waji; Fitriana; Awaluddin (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
Corona Virus Disease 2019 (Covid-19) has plagued the whole world. WHO has designated it as a disease with pandemic status. This disease attacks the respiratory system and is transmitted through droplets. The Indonesian government has issued guidelines for preventing the transmission of Covid-19 by implementing health protocols according to WHO rules. However, there are still many people who still do not believe in the existence of the Coronavirus. This makes it the government difficult to implement health protocols with standards for the community, especially in areas outside Java and Bali. Public distrust is caused by the lack of clarity of information and the large number of hoax news circulating in the community. This is also experienced by parents/guardians of students in campus Medical Laboratory of Technology, Megarezky University, most of them are domiciled in the provinces of the central and eastern parts of Indonesia. Based on these conditions, we are moved to analyze the understanding and compliance of parents/guardians of students and educate them about how to prevent Covid-19. This community service activity is expected to increase public knowledge about preventing the spread of the Covid-19 disease. The method of activity is carried out online via zoom cloud meeting and google form through three-stage are a) Initial evaluation (pre-test) to evaluate participants' understanding regarding Covid-19, b) Counseling related to education and prevention of Covid-19, c) Evaluation of understanding (post-test) Covid-19 after attending the counseling. The results of the analysis show that counseling related to education and prevention of Covid-19 can increase public understanding of the importance of implementing and maintaining health protocols, how to make disinfectants, tracking and tracing, and information on food ingredients that can increase body immunity to deal with Covid-19. The role of the institution in educating through counseling has been proven to be able to change the mindset of participants to participate in the vaccination program